'Heroes aren't always so great!' – Heroic perceptions under mortality salience. (2nd October 2019) - Schindler, Simon; Pfattheicher, Stefan; Reinhard, Marc-André; Greenberg, Jeff
ABSTRACT: According to terror management theory, in a first study ( N = 80), we tested the hypothesis that heroic perceptions of historic heroes would become more positive under mortality salience. Results, however, showed the opposite effect – heroic perceptions were less positive. To explain this unexpected finding, we referred to a social comparison perspective, assuming comparisons with a hero are likely to be unfavorable for one's self-esteem. Two further (pre-registered) studies were conducted to test this idea. Mortality salience effects in Study 2 ( N = 615) were not significant. However, using an improved experimental procedure in Study 3 ( N = 600), heroic perceptions were indeed significantly less positive under MS, especially for participants with low trait self-esteem and low social comparison orientation.